Impact of a ketamine sedation protocol on intubation rates and undesirable outcomes in the transport of patients with acute behavioural disturbance. (4th August 2019) - Shahtahmasebi, Roxanne; Johnson, Rich; Shahtahmasebi, Said
Abstract: Objectives: To identify the effects of the introduction of a ketamine sedation protocol on the rates of intubation and adverse events associated with retrieval of patients with acute behavioural disturbance. Transport of patients with acute behavioural disturbance poses clinical and logistical management difficulties, as well as risks. Remote Australian communities are separated by vast distances. Risks to aircraft and crew, and patient and community must be balanced. Ketamine has received increasing attention in recent years for pre‐hospital sedation of behaviourally disturbed patients, predominantly with psychiatric illness. This paper explores the benefits and suitability of ketamine in undifferentiated presentations, using data from the retrieval service in Alice Springs, Australia. Methods: A pre‐ and post‐intervention study was carried out. The intervention was the introduction of a ketamine sedation protocol. Pre‐intervention data was collected retrospectively, pre‐2015 and post‐intervention data prospectively from 2015 onwards. Prospective data, rather than only including confirmed psychiatric cases as in previously published series, will provide a powerful message for pre‐hospital and retrieval practice. Group variables were created to compare the incidence of adverse events. Results: The introduction of a ketamine protocol significantly reduced rates of intubation. The incidence of adverse events was strongly associated with the method of sedation ( P = 0.000, confidence interval −0.56, −0.22), with significantly lower rates with ketamine ( P < 0.0001). Conclusion: The introduction of a ketamine protocol is associated with a decrease in intubation, and accordingly, a decrease in adverse events, though it is not without its risks. Further analysis is required to establish the likely cost saving to health systems.